2015
DOI: 10.1093/bja/aev341
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant concentrations of lidocaine and ropivacaine inhibit TNFα-induced invasion of lung adenocarcinoma cells in vitro by blocking the activation of Akt and focal adhesion kinase

Abstract: At clinically relevant concentrations both ropivacaine and lidocaine blocked tumour cell invasion and MMP-9 secretion by attenuating Src-dependent inflammatory signalling events. Although determined entirely in vitro, these findings provide significant insight into the potential mechanism by which local anaesthetics might diminish metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 33 publications
3
81
0
2
Order By: Relevance
“…Piegeler et al reported that lidocaine (10 μM) and ropivacaine (1 μM) completely blocked the tumor necrosis factor α-induced increase in invasion of lung adenocarcinoma cells in vitro (28). We observed that both lidocaine and ropivacaine at 1 mM and lower concentrations had no effect on the invasion of gastric cells.…”
Section: Discussionsupporting
confidence: 44%
“…Piegeler et al reported that lidocaine (10 μM) and ropivacaine (1 μM) completely blocked the tumor necrosis factor α-induced increase in invasion of lung adenocarcinoma cells in vitro (28). We observed that both lidocaine and ropivacaine at 1 mM and lower concentrations had no effect on the invasion of gastric cells.…”
Section: Discussionsupporting
confidence: 44%
“…Src tyrosine kinase is an important enzyme in tumor growth and metastasis and controls the activation of matrix-metalloproteinases (MMP), another important factor in the pathogenesis of metastasis. Lidocaine and ropivacaine inhibited MMP9-secretion by NCl-H838 lung adenocarcinoma cells with an IC 50 of 3.3 and 1.5 µM, respectively (25). This effect of LA was independent of their primary mechanism of action, the blockade of VGSC.…”
Section: Discussionmentioning
confidence: 82%
“…Increasing intracellular calcium in PEO-1 cells reduced cell adhesiveness and also PKB/Akt is a serine/threonine kinase that has an important role in cell survival, cell proliferation, invasion, and adhesion to the ECM in various types of cells such as human umbilical vein endothelial cells 27 , breast cancer cell 28 , and lung adenocarcinoma. 29 The overexpression of PI3K/Aktrelated genes has been observed in ovarian cancer tissues. 30 Moreover, fibronectin adhesion promotes metastatic behavior on these types of cancer cells through the focal adhesion kinase-PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%